Organizational Commitment Dimensions as Predictors of Employee Communication Behavior in Moroccan Private Organizations - BOURROUK Khalid; BOUSFIHA Adiba (African Scientific Journal, 2022)
Organizational commitment and employee communication behavior have recently received an increased scholarly attention in the realm of public relations. Previous research has been oriented extensively towards examining the two constructs as antecedents or consequences of other organizational outcomes such as productivity, customer satisfaction and employee retention; however, the association between organizational commitment and employee communication behavior has not been examined. Hence, the present quantitative study purports to make a contribution to the literature by investigating the impact of organizational commitment on employee communication behavior. Specifically, three organizational commitment dimensions, namely affective, continuance and normative commitment (Meyer & Allen, 1991) were posited as antecedents to two forms of employee communication behavior, viz. megaphoning and scouting (Kim and Rhee, 2011). Using snowball sampling, 378 Moroccan employees who currently work for Moroccan private organizations took part in this study by completing a 27-item questionnaire consisting of demographic questions and items relying on a seven-point Likert scale. By deploying Pearson product-moment correlation and linear regression, organizational commitment, particularly affective and normative commitment were found to be significant predictors of employee megaphoning and scouting behaviors. The findings of this study suggest that highly committed employees are more likely to engage in positive communication behavior in their interactions with external and internal publics by voluntarily disseminating favorable information about their respective organizations (i.e. megaphoning), as well as collecting and sharing strategically useful information with management, supervisors and colleagues (i.e. scouting). Limitations of the study and recommendations for future research are addressed.